L'identité Culturelle Dans Les Nuits De Strasbourg d'Assia Djabar : Une Représentation Complexe Et Nuancée (El-Wahat Journal for Research and Studies, 2025)
The Nights of Strasbourg by Assia Djabar is a novel that deeply portrays the cultural identity and diversity in Strasbourg. Through its characters and their story, the author highlights the richness of the city's cultural diversity. Assia Djebar explores the complex themes of cultural identity and belonging in a context where individuals have often been torn between different cultures. Assia Djabar's work offers a profound reflection on the challenges faced by immigrants and their descendants in constructing their identity in a culturally diverse environment. Keywords: Identity, Cultural, The Nights Of Strasborg, Assia Djabar, Representation